Using Technology to Measure Older Adults’ Social Networks for Health and Well-Being: A Scoping Review - Wei, Sijia (Gerontologist, 2021)
BACKGROUND AND OBJECTIVES: Social networks impact the health and well-being of older adults. Advancements in technology (e.g., digital devices and mHealth) enrich our ability to collect social networks and health data. The purpose of this scoping review was to identify and map the use of technology in measuring older adults' social networks for health and social care. RESEARCH DESIGN AND METHODS: Joanna Briggs Institute methodology was followed. PubMed (MEDLINE), Sociological Abstracts, SocINDEX, CINAHL, and Web of Science were searched for relevant articles. Conference abstracts and proceedings were searched via Conference Papers Index, the American Sociological Society, and The Gerontological Society of America. Studies published in English from January 2004 to March 2020 that aimed to improve health or social care for older adults and used technology to measure social networks were included. Data were extracted by two independent reviewers using an a priori extraction tool. RESULTS: The majority of the 18 reviewed studies were pilot or simulation research conducted in Europe that focused on older adults living in the community. The various types of technologies used can be categorized as environment-based, person-based, and data-based. DISCUSSION AND IMPLICATIONS: Technology facilitates objective and longitudinal data collection on the social interactions and activities of older adults. The use of technology to measure older adults' social networks, however, is primarily in an exploratory phase. Multidisciplinary collaborations are needed to overcome operational, analytical, and implementation challenges. Future studies should leverage technologies for addressing social isolation and care for older adults, especially during the COVID-19 pandemic.